A comprehensive evaluation model for full-chain CCUS performance based on the analytic hierarchy process method. (15th January 2022) - Zheng, Yawen; Gao, Lin; Li, Sheng; Wang, Dan
Abstract: As the only resort to realize the low-carbon utilization of high-carbon fuel, CCUS has attracted considerable attention from experts in various fields. However, the global demonstration of CCUS has not gone well for several reasons. Multiple technical options, diverse combinations of schemes and complex evaluation systems of CCUS are crucial reasons. Another key point is the diverse concerns of key stakeholders involved in the deployment of CCUS, leading to decision-making difficulties. Thus, in this paper, with the aid of the analytic hierarchy process method, five representative cases are defined, compared and evaluated from the technical, economic and policy perspectives. The evaluation results and corresponding interpretations are given from diverse perspectives. By adopting this evaluation method and establishing a comprehensive model, decision makers can clarify their requirements, carry out multi-dimensional evaluation, and obtain inspiration to make corresponding judgements or decisions for early CCUS demonstration projects, which is conducive to promoting the progress of CCUS demonstration projects. Highlights: A comprehensive evaluation model for CCUS is developed with considering multiple factors. Diverse concerns of different key stakeholders are considered for further evaluation. Decision-makers can conduct assessments and get inspiration by adopting this evaluation model. Valuable implications are derived for the further deployment of CCUS demonstration projects.